2018
DOI: 10.3390/en11102546
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Vernier Permanent-Magnet Motors with Interior Permanent-Magnet Motor for Hybrid Electric Vehicles

Abstract: In this paper, three Vernier permanent-magnet (VPM) motor, namely the inner-rotor VPM (IR-VPM) motor, the outer-rotor VPM (OR-VPM) motor and the OR consequent-pole VPM (OR-CP-VPM) motor are proposed for the hybrid electric vehicle (HEV) applications. Owing to employment of toroidal-winding arrangement, the OR-VPM and the OR-CP-VPM motors can enjoy better material utilization and easier manufacturing process than its IR-VPM counterpart. Meanwhile the OR-CP-VPM motor can utilize the consequent-pole topology to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Like PMSM motors, vernier motors also typically have inner-rotor topologies and have similar disadvantages, such as long end-windings and the inefficient use of motor inner space, and to overcome these two advantages [146] proposed an outerrotor VPM using toroidal winding. A quantitative comparison among inner-rotor VPM (IR-VPM), outer-rotor VPM (OR-VPM), and outer-rotor consequent pole VPM (OR-CP-VPM) has been carried out in [147]. It is concluded that by employing toroidal winding and outer rotor topology, the motors achieve higher efficiencies and torque density.…”
Section: Inner Stator Windingmentioning
confidence: 99%
“…Like PMSM motors, vernier motors also typically have inner-rotor topologies and have similar disadvantages, such as long end-windings and the inefficient use of motor inner space, and to overcome these two advantages [146] proposed an outerrotor VPM using toroidal winding. A quantitative comparison among inner-rotor VPM (IR-VPM), outer-rotor VPM (OR-VPM), and outer-rotor consequent pole VPM (OR-CP-VPM) has been carried out in [147]. It is concluded that by employing toroidal winding and outer rotor topology, the motors achieve higher efficiencies and torque density.…”
Section: Inner Stator Windingmentioning
confidence: 99%
“…A key component of EVs is the electric motor, which should be able to provide high efficiency, high power density, high torque density, high cost-effectiveness and maintenancefree operation [9]. Most of these tasks are fulfilled by permanent-magnet motors, and 3 motor types, namely interior permanent-magnet (IPM), flux-switching permanent-magnet (FSPM) [10] and Vernier permanent-magnet (VPM) [11], are considered the most promising candidates for EV applications.…”
Section: Modern Electric Motors For Ev Applicationsmentioning
confidence: 99%
“…Different winding configurations are investigated to improve the torque production capability. An outer rotor PMVM with a hybrid excitation source is proposed in [8], in which a homopolar configuration is adopted and trickily combined the flux route of the PM with the electromagnet flux route to achieve a compact structure.…”
Section: Introductionmentioning
confidence: 99%